Studying During the COVID-19 Pandemic: Personal And Technical Aspects - Janusz GIERSZEWSKI; Andrzej PIECZYWOK; Wojciech PIESTRZYŃSKI (Communications of International Proceedings, 2021)
The coronavirus epidemic has become a signal for a profound and structural change in the functioning of higher education. A significant number of universities around the world have moved to a distance learning model, with some delivering classes in a hybrid fashion. Online classes have their undeniable advantages, but also their disadvantages. First of all, online classes at a university save time and money for students, but not always for universities, which have to maintain the infrastructure. Another disadvantage is the minimal role of social contacts. Students do not know each other, do not make friends, do not socialise after classes. You may hear that online classes are at a slightly lower level than traditional classes. The student has limited opportunities to ask questions and the teacher is not always able to read the individual needs of students. Concentration is also a problem, when the student is away from the university and can afford to follow the class with one eye and focus on other things with the other. It is impossible to not see that the COVID-19 pandemic has forced a new educational order. Universities had to make massive use of various communication technologies. Therefore, the research team decided to investigate how the problem of remote studying during the coronavirus pandemic actually looks like in the reality of Polish universities. This form of study is reflected in the connectionist theory of education based on the direct influence of the digital world on human education. The founders of this theory, George Siemens and Stephen Downes, built the concept of online learning, not as an additional tool to complement educational strategies, but as a new mental and cultural phenomenon created by the development of communication technology, so useful during the coronavirus pandemic. The aim of the research was to analyse students' opinions on the evaluation of remote education in a pandemic situation. In addition, the authors were also interested in finding out how remote education, i.e. staying away from the university and the quarantine situation affected the life and psychosocial condition of students. The analysis of students' opinions is based primarily on own research carried out at universities in Poland. Undoubtedly, this research can also be an important element of an international discussion concerning the evaluation of the form of studying online in other countries. We believe that such an approach will make this publication useful for many groups of recipients, and thus its usefulness goes beyond the issue of pandemic teaching.
Keywords: Studying; COVID-19 Pandemic; Remote Learning; Connectivism